Severity-dependent metabolic rewiring in COVID-19 based on untargeted metabolomic profiling of patient plasma - Marta Majewska; Mateusz A. Maździarz; Ewa Lepiarczyk; Aleksandra Lipka; Marta Wiszpolska; Beata Moczulska; Elżbieta Łopieńska-Biernat; Piotr Iwanowicz; Piotr Kocbach; Hilde Galtung; Leszek Gromadziński (PLoS ONE, 2026)
Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), remains a major global health challenge, characterised by a heterogeneous clinical spectrum. While metabolomic studies have identified disruptions in amino acid, lipid, nucleotide, and energy metabolism during COVID-19, these investigations often lack fine-grained clinical stratification. In this study, we performed untargeted metabolomic profiling of plasma from 25 participants, including five healthy controls and twenty COVID-19 patients classified into four severity groups (COV1–COV4) based on pulmonary involvement and the need for respiratory support. Using ultra-performance liquid chromatography coupled with mass spectrometry (UPLC-MS), 541 metabolites were detected and analysed across all samples. Principal component analysis revealed a progressive metabolic divergence corresponding to disease severity. Monocarboxylic acid dysregulation was predominant in early to moderate cases (COV1–COV3), whereas severe disease (COV4) demonstrated a shift toward pyrimidine metabolism enrichment, consistent with heightened nucleotide turnover driven by viral replication and immune cell proliferation. Phenylalanine metabolism emerged as a consistently enriched pathway in COV1–COV3, suggesting aromatic amino acid perturbations as early markers of metabolic stress and immune activation. In contrast, pyrimidine pathway activation in COV4 could reflect profound systemic metabolic reprogramming associated with critical illness. These findings provide novel insights into COVID-19 pathophysiology, highlighting stage-specific metabolic signatures and potential biomarkers for disease monitoring. Our results support the concept of metabolomics-guided precision medicine, offering a rationale for targeted therapeutic interventions based on disease stage and metabolic phenotype.